Relationship between social support and commitment to the task with academic flow to students - Kristi Tamara Novitasari; Farida Hidayati; Rini Setyowati (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2020)
This research aimed to determine the relationship of social support and commitment to the task with the academic flow of the FSRD UNS students. Research uses quantitative research methods through surveys on 300 FSRD students. The samples in this study were 271 FSRD UNS students. Sampling in this study using a proportional random sampling cluster technique i.e. the determination of sample members is carried out randomly by voting the class of each department. The data collection techniques used are psychological scales. The results showed that Fcount value is 42.303 (Fcount> Fttable 3.026) with sig. 0,000 (p <0.05) and the R value is 0.471, which means the correlation is on moderate level. The R square value is 0.222 indicating the effective contribution is 22.16%, with effective contribution of social support is 2.8% and task commitment is 19.36%. The conclusion is that there has positive correlation between social support and task commitment with academic flow.